Consequences of Ukraine signing an association agreement with the European Union - Pivchuk, Yulia (My University, 2014)
European integration of Ukraine is used in political rhetoric by almost all political forces.
Keywords: agreement; European Union; international negotiations; угода; Європейський Союз; міжнародні переговори; соглашение; Европейский Союз; международные переговоры